Rancang Bangun Sistem Informasi Penentuan Rute Dan Biaya Transportasi Pada Ukm New Sehati - Machmudah, Adisti; Susilo, Ronny S; Setyawan, Henry Bambang (Jurnal JSIKA, 2013)
Abstract: Usaha Kecil dan Menengah (UKM) New Sehati is a home manufacturing industry engaged in production of chips. Located in the area Pacet Mojokerto, home industry which is known as the central typical souvenirs of Jawa Timur has customers spread all over Jawa Timur. However, the development of UKM New Sehati is still hampered by passage of as systems are still manual recording of transactions that are still conventional and calculators, scheduling and delivery of the service is still based on the order in which influx of customers every conveyance starts and ends at the customer, and can’t to find out information sales each period. From all problems above created an information system determining the route and transportation cost of saving matrix method. The solution is built to be able to record transactions and generate arrangement delivery service to some customers based on conveyance capacity, saving mileage and fuel efficiency. After replacing the manual system with route determination information systems and transportation costs Saving Matrix based method, obtained distances decrease up to 40% shipping and transportation costs up to 30%.   Keywords: Route Determination, Transportation Costs and Saving Matrix.